The impact of dental treatment and age on salivary cortisol and alpha-amylase levels of patients with varying degrees of dental anxiety - Majed AlMaummar; Huda Othman AlThabit; Sharat Pani (BMC, 2019)
Abstract Background The purpose of this study was to assess the salivary cortisol and salivary alpha-amylase levels in children aged between 6 and 9 years, 3 months and 1 year after the successful completion of dental treatment through either pharmacological or non-pharmacological behavior management techniques. Methods A total of 1567 patients aged between 6 and 9 years who had completed dental treatment were screened. A total of 703 patients who were caries free at the end of 3 months were classified based on Frankl behavior score and administered the Arabic version of the Children's Fear Survey Schedule- Dental Subscale (CFSS-DS) and accordingly allocated to one of three groups; (Phobic Patients, Anxious Patients, Control Group). A total of 183 patients met the inclusion criteria and were followed up for 1 year. A total of 151 patients completed the study. Patients' heart rate on recall, salivary cortisol and salivary amylase were compared between the groups. Results The results of the study showed that amylase and cortisol levels had a significant association with the level of dental fear. The phobic patients had the highest levels of salivary amylase and salivary cortisol levels with no significant associations observed with either heart rate or extent of dental treatment. Control and anxious patients had significantly lower amylase levels when compared to phobic patients. There was no significant difference between the salivary cortisol levels of anxious and phobic patients. These findings were replicated on 1-year recall. Conclusions Within the limitations of this study we can conclude that salivary amylase is an indicator of of acute stress that can differentiate between anxiety and dental fear; while salivary cortisol appears to be a marker of long-term stress that lacks the sensitivity to differentiate between the two.